Dynamic Virtual Resistance Droop Control Scheme for Distributed Generation System - Junping He; Ning Wu; Liang Liang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The power quality of a low voltage distributed network is vulnerable to the plunge of a large number of distributed power sources, which could be at serious risk due to high circulating current. In order to overcome this problem, this paper proposes an active power-magnitude and reactive power-frequency droop control scheme for distributed voltage source inverters without a communication line. A novel dynamic virtual resistance control solution is demonstrated to minimize dynamic circulating current based on satisfied output voltage accuracy and stability. Differential and integral terms are added to the droop formulas to enhance the dynamic performance of the inverter and improve the stability for voltage magnitude and frequency. MATLAB simulations show that stable output voltage and small circulating current can be achieved in both grid connected mode and islanding mode by using the proposed scheme. This result is further verified by an experimental testing with two parallel voltage source inverters. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2177